Evaluation of a semi-supervised self-adjustment fine-tuning procedure for hearing aids for asymmetrical hearing loss. - Gößwein, Jonathan Albert; Chalupper, Josef; Kohl, Manuel; Kinkel, Martin; Kollmeier, Birger; Rennies, Jan (International Journal of Audiology, 2025)
Objective: This study investigated a previously evaluated self-adjustment procedure with respect to its applicability for asymmetrical hearing loss (AHL). Self-adjusted settings were evaluated for speech recognition in noise and sound preference. Design: Participants were given the possibility to adjust the left and right hearing aid separately using a two-dimensional user interface. Two different adjustment sequences were tested. Realistic everyday sound scenes in a laboratory environment were presented. The difference between the ears regarding their speech recognition in noise was tested with two spatial conditions, unaided as well as with the prescriptive formula and the self-adjusted setting. Study sample: Nineteen experienced hearing aid users (median age 76 years) with different degrees of AHL were invited to participate in this study. Results: Participants adjusted a higher gain slope across frequency in the worse ear than in the better one. The two adjustment sequences resulted in significantly different adjustment durations and gain settings. The difference between the ears regarding speech recognition in noise did not change with the self-adjustment. Overall, group-mean effect sizes were small compared to the parameter space. Conclusions: The adjustment procedure can be used also by hearing aid users with AHL to find a possibly preferred gain setting.